Calocedrus formosana Essential Oils Induce ROS-Mediated Autophagy and Apoptosis by Targeting SIRT1 in Colon Cancer Cells - Islam, Atikul; Chang, Yu-Chun; Tsao, Nai-Wen; Wang, Sheng-Yang; Chueh, Pin Ju (Antioxidants, 2024)
Colorectal cancer is the most common cancer that affects both sexes and has a poor prognosis due to aggressiveness and chemoresistance. Essential oils isolated from Calocedrus formosana (CF-EOs) have been shown to demonstrate anti-termite, antifungal, anti-mosquito, and anti-microbial activities. However, the anticancer effects of CF-EOs are not yet fully understood. Therefore, the present study aimed to explore the molecular mechanism underlying CF-EOs-mediated anti-proliferative activity in colon cancer cells. Here, cell impedance measurements showed that CF-EOs inhibit proliferation in colon cancer cells with wild-type or mutant p53. Flow cytometry revealed that CF-EOs at 20, 50 µg/mL significantly induced ROS generation and autophagy in both HCT116 p53-wt and HCT116 p53-null cell lines, whereas pretreatment with the ROS scavenger N-acetyl cysteine (NAC) markedly attenuated these changes. CF-EOs also induced apoptosis at 50 µg/mL in both lines, as determined by flow cytometry. Protein analysis showed that CF-EOs markedly induced apoptosis markers, including Trail, cleaved caspase-3, cleaved caspase-9, and cleaved PARP, as well as autophagy markers, such as the levels of ULK1, Atg5, Atg6, Atg7, and the conversion of LC3-I to LC3-II. CF-EOs were further found to inhibit the activity and expression of the NAD+-dependent deacetylase SIRT1 to increase the levels of acetylated p53 (Ac-p53) in p53-wt cells and acetylated c-Myc (Ac-c-Myc) in p53-null cells, ultimately inducing apoptosis in both lines. Interestingly, suppression of SIRT1 by CF-EOs enhanced the acetylation of ULK1, which in turn prompted ROS-dependent autophagy in colon cancer cells. The induction of apoptosis and autophagy by CF-EOs suggests that they may have potential as a promising new approach for treating cancer. Collectively, our results suggest that essential oils isolated from Calocedrus formosana act as a promising anticancer agent against colon cancer cells by targeting SIRT1 to induce ROS-mediated autophagy and apoptosis.